1983
DOI: 10.3382/ps.0621846
|View full text |Cite
|
Sign up to set email alerts
|

Feed Intake Responses of Mature White Leghorn Chickens to Changes in Feed Density

Abstract: We compared feed intake responses of White Leghorn pullets to the dilution of corn-soybean meal, mash diets with cellulose (20%) to decrease feed density and with sand (20%) to increase feed density. Although isocaloric, the intakes of the cellulose-supplemented (CS) and sand-supplemented (SS) diets differed significantly. During the initial period of 24 hr after the diets were assigned, pullets fed the CS diet consumed significantly less feed than controls while those fed the SS diet ate about the same amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…These results were in agreement with that of Wu et al (2005Wu et al ( , 2007 who reported that bird did adjust their feed intake in response to changing the levels of dietary nutrients and this is likely a response to change in dietary energy. Similar reports are also available in literature (Parson et al 1993;Cherry et al 1983). In majority of studies, increasing dietary energy decreased feed intake (Grabas et al 1999;Harms et al 2000;Wu et al 2005) and therefore improved feed conversion of laying hens.…”
Section: Discussionsupporting
confidence: 66%
“…These results were in agreement with that of Wu et al (2005Wu et al ( , 2007 who reported that bird did adjust their feed intake in response to changing the levels of dietary nutrients and this is likely a response to change in dietary energy. Similar reports are also available in literature (Parson et al 1993;Cherry et al 1983). In majority of studies, increasing dietary energy decreased feed intake (Grabas et al 1999;Harms et al 2000;Wu et al 2005) and therefore improved feed conversion of laying hens.…”
Section: Discussionsupporting
confidence: 66%
“…In an experiment with White Leghorn hens, the effect of energy density was separated from the effect of bulk density (Cherry et al, 1983) by diluting a diet with 20% wood fiber or 20% sand. Hens fed the sand diet adjusted feed intake so that caloric intake and rate of egg production were higher than for those fed the wood fiber diet.…”
Section: Discussionmentioning
confidence: 99%
“…The latter interaction occurred 7 days after a change in dietary amino acid density due to the misplacement of starter feed at the beginning of the experiment. Studies evaluating research in the literature have theorized that a 7 to 10 d adaption period is necessary for broilers to normalize feed intake ( Cherry et al., 1983 ; Leeson et al., 1996 ). The presence of these interactions may indicate that the efficiency by which the modern broiler can adapt to feed changes involving differences in nutrient density may be dependent upon the strain of broiler being fed.…”
Section: Discussionmentioning
confidence: 99%